Explaining the Relationship Between Islamic Financial Instruments and Economic Growth in the Agricultural, Industrial, and Service Sectors of the Country - Aliakbari, Farzaneh; Mirzapour Babajan, Akbar; Akbarimoghadam, Beitollah; Hadizadeh miyarkolaei, Arash (Business, Marketing, and Finance Open, 2025)
Islamic finance has emerged in the global financial literature with the aim of offering a new model to replace traditional and conventional financial systems and to provide financial, commercial, and investment opportunities aligned with Shariah principles. The main objective of the present study is to examine the impact of Islamic finance on the growth of Iran’s economic sectors. To this end, the effect of the volume of issued Sukuk and the volume of issued Islamic debt securities was investigated separately for the three economic sectors, namely industry, agriculture, and services. Accordingly, quarterly data from 2012 to 2023 were analyzed using both time series and panel data approaches. The results of model estimation showed that, under the time series approach, the impact of Sukuk financial instruments on the country's economic growth was greater than that of Treasury bills. In contrast, under the panel data approach, it was found that although the volume of Sukuk and the volume of issued Islamic debt securities had a positive and significant impact on the economic growth of the three sectors, this impact was not substantial and could not serve as a driving force for economic growth in the three sectors. In fact, the findings indicate that Islamic finance has not had a significant impact on the growth of Iran’s economic sectors. Numerous control variables have confounded the effectiveness of Islamic financial instruments. Therefore, it is expected that if macroeconomic conditions improve—including increased capital formation, improved labor force participation rates, reduced inflation, and improvements in other macroeconomic variables—the impact of Islamic financial instruments will become more pronounced and significant. Policymakers could, by ensuring the developmental effects of Islamic financial instruments, replace conventional financial instruments with Sukuk and Treasury bills and promote their broader issuance.